Prediksi Kesulitan Keuangan Menggunakan Metode Altman (Z-Score) Di Masa Pandemi Covid-19 - Wirani, Bella Nisa; Aisjah, Siti (Jurnal Management Risiko dan Keuangan, 2024)
The objective of this research is to assess the financial distress level of national television companies listed on the Indonesia Stock Exchange during the Covid-19 pandemic using Altman’s Z-score. The procedure for the financial distress assessment in this study uses the third modification of Altman’s Z-score published in 2000. The data of this quantitative research are the financial reports of national television companies during the 2019-2021 period published by the Indonesia Stock Exchange, while the sample was selected using saturated sampling technique. The results of the prediction using Altman’s Z-score show that one company was indicated for having financial distress.   The objective of this research is to assess the financial distress level of national television companies listed on the Indonesia Stock Exchange during the Covid-19 pandemic using Altman’s Z-score. The procedure for the financial distress assessment in this study uses the third modification of Altman’s Z-score published in 2000. The data of this quantitative research are the financial reports of national television companies during the 2019-2021 period published by the Indonesia Stock Exchange, while the sample was selected using saturated sampling technique. The results of the prediction using Altman’s Z-score show that one company was indicated for having financial distress.   Abstrak Penelitian ini bertujuan untuk menilai tingkat kesulitan keuangan (financial distress) perusahaan pertelevisian nasional yang terdaftar di Bursa Efek Indonesia (BEI) di masa pandemi COVID-19 dengan menggunakan metode Altman (Z-Score). Prosedur penilaian kesulitan keuangan dalam penelitian ini menggunakan rumus Altman Z-Score Modifikasi III yang dipublikasikan pada tahun 2000. Jenis penilitian yang digunakan adalah penelitian kuantitatif. Data yang digunakan dalam penelitian ini adalah laporan keuangan perusahaan pertelevisian nasional periode tahun 2019-2021 yang dipublikasikan oleh Bursa Efek Indonesia (BEI). Teknik pengambilan sampel menggunakan metode sampling jenuh. Hasil prediksi menggunakan metode Altman Z-Score terdapat satu perusahaan yang terindikasi mengalami kondisi kesulitan keuangan.